Manajemen Pendidikan, Tenaga Kependidikan, Standar Pendidik, dan Mutu Pendidikan - Susanti, Heri (STAI Auliaurrasyidin Tembilahan, 2021)
Globalization is a necessity, and its movement continues to grow and almost touches various aspects of human life, including education. However, the function of education as a part of the national character building must be maintained. Likewise, education management at the strategic, managerial, and operational levels determine the quality of education. Three aspects of educational management that are important are the issues of educational leadership, teacher standards, and education personnel which directly influence the quality of education. Predictably, effective educational leadership will support and realize the teacher standards and education personnel, which in turn will also improve the quality of education. This research focused on teachers' management, education personnel, teacher standards, and education quality. A qualitative descriptive approach was chosen as a design for this study.